Iridaaromatics via Methoxy(alkenyl)carbeneiridium Complexes - Maria Talavera; Sandra Bolaño (Molecules, 2021)
This review describes the development of a versatile methodology to synthesize polycyclic metallaaromatic hydrocarbons based on iridium, as well as the studies that helped us to determine and understand what is required in order to broaden the scope and the selectivity of the methodology and stabilize the complexes obtained. This methodology aims to open the door to new materials based on graphene fragments.